Change in CAIDE dementia risk score and neuroimaging biomarkers during a 2‐year multidomain lifestyle randomized controlled trial: Neuroimaging / evaluating treatments. (7th December 2020) - Stephen, Ruth; Ngandu, Tiia; Liu, Yawu; Peltonen, Markku; Antikainen, Riitta; Kemppainen, Nina; Laatikainen, Tiina; Lötjönen, Jyrki; Rinne, Juha O.; Strandberg, Timo; Tuomilehto, Jaakko; Vanninen, Ritva; et al.
Abstract: Background: The Cardiovascular Risk Factors, Aging, and Incidence of Dementia (CAIDE) risk score was the first validated risk score estimating dementia risk based on a midlife risk profile. This exploratory study investigated associations of change in CAIDE score with change in neuroimaging biomarkers: brain magnetic resonance imaging (MRI) and Pittsburgh compound B‐positron emission tomography (PiB‐PET) measures during the 2‐year Finnish Geriatric Intervention Study to prevent cognitive impairment and disability (FINGER). Method: FINGER targeted an at‐risk 60‐77 years old general population without dementia/substantial cognitive impairment. Data from baseline and 2‐year visits were used. 112 participants (59 intervention, 53 control) had repeated brain MRI measures (hippocampal, total gray matter, and white matter lesion volumes, and Alzheimer's disease (AD) signature cortical thickness). Repeated PiB‐PET scans were available for 39 participants (18 intervention, 21 control). Linear regressions were used to test the association of CAIDE score change with change in MRI and PiB‐PET measures. Result: Reduction in CAIDE score was associated less decline in hippocampus volume in the intervention group, but not the control group (randomization group x CAIDE change interaction β‐coefficient= ‐0.40; p=0.02). Associations for other MRI measures and amyloid accumulation on PiB‐PET scans were not significant. Conclusion: Reduction in estimated dementia risk as indicated by the CAIDE score change may result in more pronounced intervention benefits on hippocampus volume. Findings from this study should be verified in clinical trials with larger neuroimaging sample sizes and longer follow‐up.